Programmed Cell Death in Immune Defense: Knowledge and Presumptions - Wallach, David; Kang, Tae-Bong (Immunity (Cambridge, Mass.), 2018)
Cell-culture studies are our main source of knowledge of the various forms of programmed cell death. Yet genetic perturbations of death-protein function in animal models are almost the only source of our knowledge of the physiological roles of these programs. Shortcomings in the state of knowledge acquired by these two experimental approaches are exemplified in this Perspective by reference to research on the contribution of apoptosis to lymphocyte development, a subject on which there is already much knowledge, and on the role of necroptosis in inflammation, about which information is just beginning to emerge. To address these shortcomings, there is need to find ways to verify the notions obtained through the current experimental approaches by directly monitoring death programs within specific cells in vivo. Cell death mechanisms have mainly been studied in vitro. Exploring their roles in immune defense in vivo has been done largely by indirect means. Wallach and Kang provide a perspective of the limitations of these means in studying the roles of apoptosis in lymphocyte development and of necroptosis in inflammation.